1964
DOI: 10.2134/agronj1964.00021962005600030028x
|View full text |Cite
|
Sign up to set email alerts
|

End‐Border Effects in Irrigated Barley Yield Trials1

Abstract: OMPETITION and border effects are recognized as C sources of error in agronomic experiments (1, 5 , 10, 11). Most research experiments regarding border effects have been designed to study side-border effects in nonirrigated areas. Additional research is needed to determine the magnitude of end-border effects under irrigated conditions. REVIEW OF LITERATURE Border effects have been studied in a number of different crops. Green (6) , Drapala and Johnson (5) , and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…1000-grain weight was the least affected. Similar results were found by Bhalli et al (1964) and Brown & Weibel (1957).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1000-grain weight was the least affected. Similar results were found by Bhalli et al (1964) and Brown & Weibel (1957).…”
Section: Discussionsupporting
confidence: 90%
“…As expected, yields were higher when whole plots were harvested than when the border rows, adjacent to the pathway, were removed before harvesting (Bhalli et al 1964;Fischer, 1979Fischer, , 1981Austin & Blackwell, 1980). Several other studies examined the effects of border rows in continuous sowing of varieties (no uncropped pathways between them), using different crops (cited by Jensen & Federer, 1964, 1965Rich, 1973).…”
Section: Introductionmentioning
confidence: 69%
“…Considering the optimal design for v � 5, p � 5 obtained from the set of shifts [1, 2, 3]t; the following are the matrix L, matrix M, and N matrix of the CBRMD (Table 2). [19,16,21,14,23,12,25,10,27,8,29,6,31,4,33,2,35,18,1,34,3,32,5,30,7,28,9,26,11,24,13,22,15,20,17]t…”
Section: □ Theoremmentioning
confidence: 99%
“…Repeated measurements designs (RMDs) have wide applications to ensure the validity and reproducibility of research in plant breeding and genetics research. Such designs have been extensively applied in areas where the treatment could be a plant variety, fertilizer, irrigation, or pesticide [1][2][3]. In crop experiments, the neighbor e ects have been recognized by Haines and Benzian [4] as well as Jenkyn and Dyke [5] due to competition for light, poaching of nutrients by plant roots, and the spread of disease pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Vernon [14] found substantial neighbour effects when plots receiving different manurial treatments were adjacent. Irrigation experiments are also liable to produce large neighbour effects; Bhalli et al [2] describe an example of this in the arable crop situation. They found that the neighbour effect varied between different varieties of barley, leading to substantial errors in the ranking of the varieties when the plot edges were included.…”
Section: Neighbour Effectsmentioning
confidence: 99%